Design of JKN Claim Information System for Outpatient BPJS Patients with SDLC Method - Khoirunnisa, Diana; Rahayu, Fitri Mardiani; Syahidin, Yuda; Sari, Irda; Yuniarty, Neneng (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
BPJS claim is the submission of all BPJS patient care costs by the Hospital to the BPJS Health, carried out collectively and billed to the BPJS Health every month through the verification process. BPJS Health is a legal entity established to administer the Health Insurance program. Health Insurance is a guarantee in the form of health protection so that participants obtain health maintenance benefits and protection in meeting basic health needs provided to everyone who has paid contributions or whose contributions are paid by the government. This study aims to design a medical record management system to support JKN claims for outpatients at Muhammadiyah Bandung Hospital. The research method used in this research is qualitative with a descriptive approach. The data collection techniques used were interview, observation and literature study. The results showed that there were problems that occurred, namely unclear resumes, illegible SEPs, missing referral letters, and there was still 1 outpatient period that was mixed up so that coding officers found it difficult to read it and became an obstacle to claiming. Based on this research, it can be concluded that there is a need for a quality audit of specific medical resume writing and incomplete BPJS patient requirement files.